Prognostic value of the leuko-glycemic index in coronary chronic total occlusion patients - Peker, Tezcan; Özbek, Mehmet; Boyraz, Bedrettin; Aslan, Selen Filiz; Demir, Muhammed; Aslan, Burhan (The European Research Journal, 2023)
Objectives: Inflammation parameters are related to the prevalence and mortality of coronary artery disease (CAD). We aimed to evaluate the prognostic value of the leuko-glycemic index (LGI) and determine mortality in patients with chronic coronary total occlusion (CTO). Methods: A total of 546 patients were evaluated in the study. All-cause death was the primary endpoint. The leuko-glycemic index was calculated from the blood samples at admission and patients were divided into 3 groups according to their LGI levels. Kaplan-Meier survival curves were performed and logistic regression analyses was used for all multivariable analysis. Results: The mean age of the study population was 63.1 ± 11.1 years and 70.3% were male. Median follow-up time 58.2 ± 22.4 months. The mortality rate was 33.6% in the high LGI group and significantly higher compared to the other group. In multivariable analysis, LGI (OR: 1.05, 95% CI: 1,0-1.2; p = 0.02) and age (OR: 1.07, 95% CI: 1.04-1.11; p = 0.001) were found as predictors of all-cause death. Conclusions: The study revealed that high LGI is associated with all-cause death in CTO patients and LGI was a predictor of all-cause death.